Esophageal hiatus surgery. Videolaparoscopic approach.: Analysis of CRAMI cholecystectomies in 1999 - Montano, Daniel; Polnitsky, José; Pisano, Alberto; Navarro, Teodoro; Abascal, Winston; Vallverdú, Martín; Varela, Daniel; Olivera, Eduardo; Bordes, Daniel; Canessa, César; Crestanello, Francisco (Cirugía del Uruguay, 2003)
The authors present 107 colecystectomies performed in CRAMI during 1999 for gallstone disease. 52 were laparoscopic colecystectomies and 55 open colecystectomies, 24 in the urgency. The length of stay was 1.04 days for the laparoscopic colecystectomies and 3.06 and 4.04 for open colecystectomies in coordinated an urgency procedures. Less than 1/5 of analgesic and antibiotic were needed in lapároscopic colecystectomies.